Anthony Faulkes and Richard Perkins (ed.): Viking Revaluations. Viking Society Centenary Symposium 1992. (Viking Society for Northern Research, 1993). 216 s., 20 £. - Malmros, Rikke (Historie/Jyske Samlinger, 1995)
-